ФУНКЦІЇ СУБ’ЄКТІВ АГРОБІЗНЕСУ В ДОТРИМАННІ КАДРОВОЇ СКЛАДОВОЇ СОЦІАЛЬНО-ЕКОНОМІЧНОЇ БЕЗПЕКИ (International Journal of Innovative Technologies in Economy, 2018)
The article highlights the substantiation of the functions of the subjects of agribusiness as components of the socioeconomic security of enterprises in the system of personnel potential formation. The analysis of the current situation at the enterprises of agricultural production, outlines the problems of preparation of skilled personnel and gives grounds for defining a list of tasks for the functional observance of personnel security. The emphasis is on the need to strengthen the role of training employees in enterprises in the process of their work.